Preliminary data on the morphology and karyotype Noemacheilus labiatus (kessler, 1874) Ile-Balkhash Basin (Eurasian Journal of Ecology, 2016)
The paper deals with the morphological characteristics of the three populations and karyology Noemacheilus labiatus Ile- Balkhash basin. Morphological analysis showed that among populations of stone loaches River Bridge 2 ( tributary Karatal ) and Ile river observed significant differences in two ways : the number of rays in the pectoral fins (M diff = 3,59) and anterodorsal distance (M diff = -3,77). By geometrical parameters were revealed differences between males and females : males are larger than females and are characterized by 4 plastic signs – maximum body height, length of dorsal fin, length of the upper lobe of the caudal fin and the distance between the lobes of the caudal fin. Karyotype color gubach, like all members of the family Noemachelidae, is diploid set of 50 chromosomes. Preliminary data indicate differences in the formula karyotype not only between species, but also between different populations of thesame species.
Keywords: plain sloth; population; morphological analysis; karyotype